The current status of the implementation of Republic Act no. 9242 or the Philippine Tropical Fabrics Law Ma. Monica E. Rayala, adviser. - Salanga, Angel Antonio C. III (College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT In 2004, the Republic Act No. 9242 also known as the Philippine Tropical Fabrics Law was enacted. Part of the mandate of the law is to require all government offices and employees to use Philippine Tropical Fabrics, which are defined as locally sourced, spun, manufactured and produced textiles with fiber contents of pineapple, abaca, banana and or silk, as official uniforms and for other official government uses. However, ten years have passed since its enactment; the law is still yet to be fully implemented. This study aims to determine the current status of the implementation of the Philippine Tropical Fabrics Law; to also identify specific sectors involved, assess each sector?s role in the implementation and to determine specific issues and problems facing its full implementation. To be able to know why the law has yet to be fully implemented and to know what can be done is important as we evaluate the current state of the Philippine textile industry in which Philippine Tropical Fabrics are poised to be the answer to its revitalization. The study is a descriptive evaluative type of research that deals with qualitative data gathered in large part from purposive personal interviews and communications of the researcher to seven of the most involved industry personnel in the implementation of the law. This research shows that the current state of the implementation of the Philippine Tropical Fabrics Law is still in the process of procuring enough supply of the fabrics as problems in degumming and pre-treatment of the fibers proved to be the main cause why there has been little production of the Philippine Tropical Fabrics. Add to that the less than satisfactory participation and involvement of private investors in producing the fabrics due to high investment costs. It is clear that the law needs to be restructured and re-amended in order to give a clearer set of responsibilities and flexible authority to its implementing agencies for a more effective result.